ANALYSIS OF STUDENT SATISFACTION WITH LECTURERS' TEACHING PERFORMANCE BASED ON ADEPT PERFORMANCE STANDARDS FOR CLASSROOM-BASED TEACHERS: THE CASE OF INDONESIAN HIGHER UNIVERSITY STUDENTS - Muslim, Abdul Qadir; Fanani, Muhammad Adip; Hayat, Ainul (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This research is motivated by the decline in student satisfaction with lecturers' teaching performance as evidenced by the decline in the results of the EDOM (Lecturer Evaluation by Students) survey for the Education Administration Study Program in a row over the last three years and the results have never been officially published among students regarding the results. Student satisfaction is an important factor in assessing the performance provided. The aims of this research are 1) to determine and analyze the level of student satisfaction with teaching performance. 2) to identify and analyze dimensions of lecturers' teaching performance that are considered important by students to map out the priority order for improving the teaching performance of lecturers in the Educational Administration Study Program. This research uses descriptive research with a quantitative approach. Meanwhile, the method used in this research uses a survey method. Data collection was carried out by distributing questionnaires with instruments based on the ADEPT Performance Standards for Classroom-Based Teachers. The data analysis technique in this research uses descriptive analysis and Importance Performance Analysis which is processed using the SPSS 21 program. The results of this research show that 1) the level of satisfaction with the teaching performance of Lecturers in the FIA UB Educational Administration Study Program is classified as very satisfied, namely with a percentage of 85.21% 2) dimensions of teaching performance that are considered important by students and are priorities for improving teaching performance, namely the dimensions of teaching and the classroom environment as indicated by these dimensions are included in quadrant I category on the Importance Performance Analysis analysis diagram.